Dynamic Oligopoly with Sticky Prices: Closed-Loop, Feedback and Open-Loop Solutions - Roberto Cellini; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
We investigate a dynamic oligopoly game with price adjustments. We show that the subgame perfect equilibria are characterised by larger output and lower price levels then the open-loop solution. The individual (and industry) output at the closed-loop equilibrium is larger than its counterpart at the feedback equilibrium. Therefore, firms prefer the open-loop equilibrium to the feedback equilibrium, and the latter to the closed-loop equilibrium. The opposite applies to consumers.
Keywords: 330